Analysis of Motivation, Competence, Compensation and Work Discipline: Their Influence on Performance Moderated by Employee Career Development (Study at Samarinda City Secretariat) - Nufuf, Galuh Hayatun; Rachman, Marjoni; Ruliana, Titin (Journal of Public Representative and Society Provision, 2025)
This study aims to analyze the influence of motivation, competence, compensation, and work discipline on employee performance through career development at the Secretariat of Samarinda City. The theoretical framework integrates human resource management principles emphasizing operational efficiency, employee empowerment, and sustainable career growth. A quantitative research method was employed, involving 339 employees from various departments within the Secretariat as the study population. Data collection utilized structured questionnaires, and analysis was conducted using Structural Equation Modeling (SEM) with Partial Least Square (PLS) software. The study focused on relationships among independent variables (motivation, competence, compensation, and work discipline), the mediating variable (career development), and the dependent variable (employee performance). Findings indicate that motivation, competence, and compensation significantly affect career development and employee performance, while work discipline impacts performance directly but not significantly through career development. Career development was also found to have a significant positive effect on employee performance. The research highlights the necessity of structured career development programs and effective HR management strategies to enhance employee outcomes.